Promoting intercultural competence and social awareness through cooperative activities in higher education - Martínez Lirola, María (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
ABSTRACT This study aims to provide a teaching proposal that highlights the importance of intercultural competence and social issues in ELT. This article offers some activities to introduce cultural aspects and social topics in an English subject taught in the degree in English Studies. For its framework of analysis, the study draws on a competence-based curriculum, so that students develop social awareness and critical thinking at the same time as they become intercultural citizens. A survey was prepared to find out students’ opinions about the methodology used and the competences they had acquired. The study reveals that introducing intercultural competences and social awareness helps students be aware of social realities and offers opportunities for them to be respectful of cultural differences.